2008
DOI: 10.1093/ije/dyn113
|View full text |Cite
|
Sign up to set email alerts
|

Smoking increases the risk of relapse after successful tuberculosis treatment

Abstract: Background Recent tobacco smoking has been identified as a risk factor for developing tuberculosis, and two studies which have investigated its association with relapse of tuberculosis after completion of treatment had conflicting results (and did not control for confounding). The objective of this study was to investigate risk factors for tuberculosis relapse, with emphasis on smoking.Methods A cohort of newly diagnosed TB cases was followed up from their discharge after completion of treatment (in 2001–2003)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…11 Smoking might complicate anti-tuberculosis treatment through poor TB outcomes (e.g., relapse after treatment). 42 The association between smoking and TB may also be responsible for some of the effects observed between excess alcohol use and the outcomes in the current study.…”
Section: Discussionmentioning
confidence: 73%
“…11 Smoking might complicate anti-tuberculosis treatment through poor TB outcomes (e.g., relapse after treatment). 42 The association between smoking and TB may also be responsible for some of the effects observed between excess alcohol use and the outcomes in the current study.…”
Section: Discussionmentioning
confidence: 73%
“…A consistent study has shown that smokers are 2.5 times more likely to have a recurrence than nonsmokers 2 . Thus, the relationship between smoking, previous treatment of TB (recurrence), and resistance to anti-tuberculosis drugs deserve to be better investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is an established association between cigarette smoking and TB treatment outcomes including an increased risk of death (28) and an increased risk of relapse after successful completion of treatment (29). A recent study from Korea showed that DM and smoking independently increased the risk of death in TB patients, with the combined impact of both determinants yielding a hazard ratio for death of almost six (30).…”
Section: Discussionmentioning
confidence: 99%